GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 94835 species occurrences available in GBIF matching the query: TaxonKey: Carabus Linnaeus, 1758. The dataset includes 94835 records from 320 constituent datasets: 5 records from International Barcode of Life project (iBOL). 34 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 10 records from Insect Collection (CeStuBio). 1 records from Inventory and BioBlitz Records from rare Charitable Research Reserve. 96 records from Alterra (NL) - Entomofauna inventory in cattle grazed dune grassland. 104 records from Alterra (NL) - Entomofauna inventory in peat swamps. 1 records from The Environmental Sample Collection of the Arthropoda Varia Section at the Zoologische Staatssammlung München. 2 records from Dorset Environmental Records Centre - Dorset SSSI Species Records 1952 - 2004 (Natural England). 3 records from Coleoptera of Swierklaniec Forest. 5 records from ColRest_Raw1. 1220 records from Zoology (Museum of Evolution - Uppsala). 7 records from PlutoF platform observations. 74 records from Likona Invertebrates. 574 records from Carabidae of the Tatra Mts.. 1 records from Local BioBlitz Challenge 2013. 174 records from Highland Biological Recording Group - HBRG Insects Dataset. 829 records from Lund Museum of Zoology - Insect collections (MZLU). 99 records from Inventario Español de Especies Terrestres (MAGRAMA). 558 records from Entomology, Natural History Museum, University of Oslo. 250 records from Hosted Invertebrate Collection 01. 4 records from Ontario BioBlitz Species Records. 139 records from BioFokus. 2 records from Bioblitz 2013 Copenhagen Denmark. 29 records from Royal Horticultural Society - Records from the RHS insect reference collection. 365 records from NINA insect database. 5385 records from Artdata. 1760 records from Données ONF Faune-Flore-Fonge. 15 records from Zur Faunistik und Ökologie der Caribiden (Caribidae, Coleoptera) ausgewählter Trockenstandorte in der 'Nuthe-Nieplitz-Niederung' (Land Brandenburg). 1 records from Norwegian Biodiversity Information Centre - Other datasets. 3 records from arim. 30 records from Museum of Comparative Zoology, Harvard University. 529 records from Staatliches Naturhistorisches Museum Braunschweig - Coleoptera Collection. 682 records from Kyushu University Museum Coleoptera Collection. 141 records from iNaturalist Research-grade Observations. 3 records from Outer Hebrides Biological Recording Project - OHBRP Insects Dataset - Outer Hebrides. 39 records from Recent Invertebrates Specimens. 6 records from Merseyside BioBank - Merseyside BioBank Active Naturalists (unverified). 30 records from Estonian Museum of Natural History. 647 records from mel. 762 records from Estonian University of Life Sciences. 15 records from Essig Museum of Entomology. 61 records from NMNH occurrence DwC-A. 1 records from Kloster Eberbach. 1 records from Hainhoop - Tonkuhle - Bullenmoor (Arpke). 1 records from Kiesgruben Wemb. 1 records from Stadtpark Herzberg (Elster). 2 records from Schulgelände Gebrüder-Grimm-Schuleund Umgebung (Lingen). 1 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 1 records from Hainbachtal in Oelsnitz/V.. 1 records from Umgebung der Grundschule Oderberg. 1 records from Steinbruch Mainz-Weisenau, 2. Jahr. 1 records from Alter Kreidebruch Saßnitz/Rügen. 1 records from Rund um das LUGY. 1 records from Schulgarten Hans-Carossa-Oberschule. 3 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 1 records from Ökologischer Weinberg (Guntersblum). 1 records from Hangwiese bei Tussenhausen Klassen 1 a und 1 b. 1 records from Schulgartengelände des Hans-Carossa-Gymnasiums (Berlin). 1 records from Dorfrand Mauderode. 1 records from Artensuche auf den Elbwiesen in Radebeul. 1 records from Schulhof der Astrid-Lindgren-Schule Elmshorn. 1 records from Flächennaturdenkmal Grubditz. 1 records from Saalewiesen Naumburg. 3 records from Dalbekschlucht. 1 records from Waldstück Bremerhagen LK Bio Kl. 12. 1 records from Gelände des Schulzentrums am Himmelsbarg. 2 records from Biosphäre Bliesgau. 2 records from Stausee Weiditz. 1 records from Garten in Schmölln. 1 records from Regenwasserabfangbecken. 1 records from Schulgelände Hans-Carossa-Gymnasium (Berlin). 1 records from Hoher Stein Kallenhardt. 2 records from Mühlenbach bei Buxtehude. 1 records from Estetal (Buxtehude). 1 records from Sudeniederung (Amt Neuhaus). 1 records from schlittschuhweiher. 1 records from Kirchheller Heide ( Bottrop). 160 records from Dpto. de Zoologia y Antropologia Fisica, Universidad de Murcia. 1 records from FFH-Gebiet "Calwer Heckengäu". 1 records from Schulgelände Paul-Gerhardt-Schule. 14 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 1 records from 10. GEO - Tag der Artenvielfalt 2008 - LSG "Pfarrhübel" Chemnitz. 1 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1 records from LK 11 im Mönchspark. 1 records from Schulwald Marksuhl. 7 records from Alterra (NL) - Comparison entomofauna in cities en countrysides. 2 records from FFH-Gebiet Klosterwasser/Burkau. 1 records from Gronau - auf der Suche nach dem Neunauge. 1 records from Liether Park 1 (LMS), Klasse 5b. 1 records from Unter hellen Zinnen und finsteren Grotten. 1 records from Feuchtwiese Grüne Mitte, Klasse 5a. 130 records from European riparian ground beetles. 1 records from Naturalis Biodiversity Center (NL) - Micropaleontology. 31 records from Biodiversity records from Ireland - general. 97 records from University of Ghent - Zoology Museum - Invertebratacollectie. 6 records from Illinois Natural History Survey Insect Collection. 40 records from Coleoptera collection of Uunio Saalas. 14475 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 638 records from naturgucker. 2054 records from Entomological collections, UiB. 10 records from New Zealand Arthropod Collection (NZAC). 140 records from Royal Horticultural Society - RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 15 records from National Trust - Hatfield Forest species data held by The National Trust.. 23 records from Biodiversity Institute of Ontario (BIOUG). 1 records from Coleoptera identified from the Poplar High Street site, Tower Hamlets, London. 2 records from Coleoptera identified from the Horton Kirby site, near London. 1 records from Biosphärenpark Wienerwald - Pfaffstätten. 1 records from Kühmark bei Wetzlar. 2 records from GEO-Hauptveranstaltung in "Wildtierland". 1 records from Schriesheimer Steinbruch. 1 records from Artenvielfalt in der Kinderakademie im RFZ. 1 records from Artenerfassung für Jedermann in der Grundschule Kirchboitzen. 1 records from GEO-Tag am Hohlen Stein. 1 records from Naturpark Kottenforst-Ville 18.6.09. 3 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 1 records from Dornwanger Moos. 1 records from Naturpark Kottenforst-Ville 15.6.09. 1 records from Naturpark Kottenforst-Ville 19.6.09. 1 records from Streuobstwiese Stedar 2009. 1 records from Liether Park (LMS), 6c. 2 records from Biotope entdecken im Kockmecker Siepen (Sauerland). 1 records from Naturpark Kottenforst-Ville 16.6.09. 1 records from NABU-Fläche am Bösselhausener Weg. 1 records from Naturgarten Vielfalt - Naturlehrgarten Fa. Dehner. 3 records from Wiesen in der Grünen Mitte. 2 records from MfN - Fossil invertebrates III. 974 records from Coleoptera. 2257 records from Insekten Sachsen. 410 records from Field Museum of Natural History (Zoology) Insect, Arachnid and Myriapod Collection. 1 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 4 records from Taiwan Forestry Research Institute. 22 records from IMEDEA-INSECTA. 1 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 219 records from Museu de Ciències Naturals de Barcelona: MCNB-Art. 100 records from Colección de Entomología del Museo de Ciencias Naturales de Tenerife: TFMC-EN. 256 records from Coleopteran specimens of Iwate Prefectural Museum. 27 records from Akita Prefectural Museum, Insect Collection. 8 records from Insect Specimens deposited in the Saga Pref., Space and Science museum, JAPAN. 1 records from Artenvielfalt rund um die Dalbek-Schule. 1 records from Fliegenhaupt Marksuhl. 1 records from Grünes Germersheim. 1 records from Sukzession Industriebrache. 153 records from Insect (NSMK-IN). 15 records from Insect (HUNM-IN). 330 records from Insect (JNHM-IN). 21 records from Insect (JJHA-IN). 12 records from Insect (MNHM-IN). 3 records from Insect (GNHM-IN). 500 records from IZIKO South Africa Museum Collection (1800-2013). 1920 records from Ehime University Coleoptera Collection. 178 records from SysTax - Zoological Collections. 105 records from Alterra (NL) - Entomofauna inventory in Speulder forest. 20 records from Naturhistorisches Museum Mainz, Zoological Collection. 32 records from Natural History Museum (London) Collection Specimens. 139 records from Coleoptera collection, NHM. 1 records from Computarización de la Colección Nacional de insectos Dr. Alfredo Barrera Marín del Museo de Historia Natural de la Ciudad de México. Coleóptera. 1 records from NatureServe Network Species Occurrence Data. 373 records from UAM Insect Collection (Arctos). 16 records from Ireland's BioBlitz. 3 records from Colección científica del Museo de Historia Natural Alfredo Dugés. 2 records from KNWR Entomology Collection. 68 records from Ibaraki Nature Museum, Arthropoda collection. 325 records from Naturkundemuseum im Ottoneum Kassel, Entomological Collection. 10 records from Interactive Database of Biodiversity Studies on Terrestrial Arthropod Animals of Korea. 152 records from Laboratorio de Entomología y Control de Plagas del Instituto Cavanilles de Biodiversidad y Biología Evolutiva de la Universidad de Valencia: ENV. 702 records from Naturalis Biodiversity Center (NL) - Coleoptera. 1 records from Paleobiology Database. 1448 records from Kashihara City Museum of Insect. 181 records from Insect Specimen Database of Fukui City Museum of Natural History. 664 records from Osaka Prefectural Minoh Park Insects Museum. 308 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 6 records from Entomology Department Collections, Natural History Museum of Denmark. 2 records from GEO Biodiversity Day. 4910 records from Biologiezentrum Linz. 2031 records from Database of invertebrates collected in Mongolia. 19 records from Insect specimens of Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 714 records from Insect Specimens of Taga Town Museum, Shiga Pref., Japan. 261 records from Coleoptera specimen database of Osaka Museum of Natural History. 31 records from Itami City Museum of Insects. 13 records from Staffordshire Ecological Record - SER Site-based Surveys. 407 records from Banc de dades de biodiversitat de Catalunya-ArtroCat. 1 records from CNIN/Tipos Coleoptera. 1046 records from University of Alberta E. H. Strickland Entomological Museum (UASM). 1 records from BÜG. 1 records from LaBoOb02. 2 records from Klutensee. 2 records from Überall ist Wunderland. 1 records from DJH. 2 records from Am Moosangerweg. 2 records from Danielsberg (Mölltal, Kärnten). 5 records from Naturschutzgebiet Sistig-Krekeler-Heide. 2 records from Botanischer Garten (Saarbrücken). 2 records from GEO-Hauptveranstaltung (NLP Harz / Hochharz). 3 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 4 records from Kernberge und Umgebung (Jena). 3 records from Mooswald (Freiburg). 2 records from Gemeinde Sursee. 5 records from Gewann Krampf (Heilbronn). 1 records from Landschaftspflegehof (Berlin). 1 records from Naturschutzgebiet Bausenberg. 1 records from Schulhof Bühlschule Giengen. 2 records from Schlern - (Bozen). 5 records from GEO Hauptveranstaltung Tirol (Innsbruck). 4 records from Königstetten. 1 records from Erzental (Oberotterbach). 1 records from Langes Tannen (Uetersen). 1 records from Stausee (Oberdigisheim/Meßstetten). 1 records from NSG Hülenbuch Hörnle (Tieringen/Meßstetten). 2 records from Langes Tannen. 1 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 1 records from Blumenrather Heide / Virneburg. 7 records from Cuxhavener Küstenheiden. 6 records from Artenvielfalt auf der Weide - GEO-Hauptveranstaltung in Crawinkel. 1 records from Danisco-Wiese. 1 records from nazza. 1 records from GEO-Hauptveranstaltung (Insel Vilm). 1 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 1 records from Unser Schulgelände. 2 records from Sudeniederung (Amt Neuhaus), Landkreis Lüneburg. 1 records from Riedensee. 1 records from Streuobstwiese Kattenhund (Schleswig). 1 records from Überschwemmungsgebiet der Wied. 1 records from 20 Jahre Naturschutzgebiet Dreienberg. 1 records from Biotope auf dem Gelände der Eggerstedt- Kaserne in der Nachbarschaft der Theodor-Heuss-Schule. 1 records from NABU Naturschutzhof Netttetal (Sassenfeld) e.V.. 1 records from Kiesbagger (Mittelhausen). 2 records from Biotop Binsenwiesen (Wehrheim/Taunus). 1 records from NSG Berschau - Auengebiet (Neustadt / Wied). 2 records from Fels- und Weinbergsflächen in Hatzenport/Terrassenmosel. 1 records from Faberpark (Nürnberg/Stein). 1 records from Unser Schulhof. 2 records from Geo-Tag der Artenvielfalt Süßen Hornwiesen-Grundschule. 1 records from Wismar Bucht coast-watching. 58 records from Colorado Plateau Museum of Arthropod Biodiversity. 4 records from Feriendorf des Kreises Groß-Gerau Ober-Seemen/Gedern. 1 records from renaturierter Main (Kemmern bei Bamberg). 1 records from Spandau HBO. 1 records from Dreilinden Gymnasium-Schulgelände. 1 records from Himmelmoor. 1 records from Freigelände Naturschutzscheune Reinheimer Teich (Kreis Darmstadt-Dieburg). 4 records from Walldorf-Wiesloch: "Natur über den Gleisen". 1 records from Naturgarten Langenholtensen. 1 records from Feriendorf des Kreises Groß-Gerau/Ober-Seemen. 1 records from Schulgelände SGD/Viersen. 295 records from Natural History Museum, University of Tartu. 3 records from Perchtoldsdorfer Heide. 1 records from Leben in und an der Ruwer sowie ihren Nebenbächen. 2 records from Biosphärenreservat Münsinger Alb. 1 records from Waldstück am Schullandheim Bad Bederkesa. 1 records from Waldwandel in Monschau-Mützenich-Boverei. 47 records from EDIT - ATBI in Mercantour/Alpi Marittime (France/Italy). 32 records from EDIT - ATBI in Gemer area (Slovakia). 15 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 737 records from Invertebrate collection of Jyväskylä University Museum. 82 records from Gunma Museum of Natural History, Insect Specimen. 360 records from Insect Collection of Natural History Museum and Institute, Chiba. 2 records from Artenvielfalt am Schlern. 40 records from Colección del Departamento de Biología Animal (Zoología) de la Universidad de La Laguna. 859 records from Biological and palaeontological collection and observation data MNHNL. 4 records from Entomology Division, Yale Peabody Museum. 32 records from Collection Coleoptera SMF. 20 records from Insect Arthropods (KIDR-IN). 43 records from Entomological Collections (NHRS), Swedish Museum of Natural History (NRM). 39 records from Carabidae of Wales and England. 13026 records from Insect (KNAM-IN). 18 records from Museum of Southwestern Biology, Division of Arthropods. 293 records from Finnish Entomological Database: Coleoptera. 1 records from Inventaire National du Patrimoine Naturel : Inventaire du Parc national du Mercantour. 50 records from Carabidae on grasslands 2008. 8 records from Coleoptera of Biebrza National Park. 112 records from ArtenFinder. 5 records from Snow Entomological Museum Collection. 5 records from National Trust - Ickworth species data held by The National Trust.. 500 records from Geographically tagged INSDC sequences. 195 records from Coleoptera collection of National Museum of Nature and Science. 699 records from Norwegian Species Observation Service. 6 records from The fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 466 records from Northern Biodiversity Program Coleoptera (2010-2011). 1 records from Fauna and flora inventories (terrestrial and limnetic) from the South of Belgium. 8 records from DNSM: Durban Natural Science Museum Insect Collection (1900-2011). 23 records from Staffordshire Ecological Record - SER Species-based Surveys. 4 records from Insect Collection of Taiwan Forestry Research Institute. 6 records from Coleoptera of Tuchola Forest and Tuchola Forest National Park. 6 records from Instituto de Ciencias Naturales. 2 records from UCMC_Entomology. 38 records from Estonian Nature Observations Database. 72 records from Hokkaido University Coleoptera Collection. 47 records from Ájtte. 6524 records from Carabidae of the Carpathians. 15 records from Birds of Cisna Community (southern Poland). 421 records from Ghent University - Zoology Museum - Insect collection. 340 records from Countryside Council for Wales - Welsh Invertebrate Database (WID). 366 records from NIAES Coleoptera Specimen Database. 1760 records from Données ONF Faune-Flore-FOnge. 105 records from National System of Protected Areas in Poland - Animals. 259 records from Natural History Museum Rotterdam (NL) - Insecta collection. 1 records from Ecofact. 4 records from Alterra (NL) - Entomofauna inventory in riverside grasslands. 74 records from Nijmegen Natural History Museum (NL) - Entomological Collection. 73 records from Alterra (NL) - Comparison of entomofauna in four different habitats. 3 records from Entomology at ZMUC, Natural History Musem of Denmark. 1 records from National Trust - Heigham Holmes species data held by The National Trust. 2 records from BoBO - Botanic Garden and Botanical Museum Berlin-Dahlem Observations. 575 records from Insect collection of Biodiversity Center of Japan, Ministry of the Environment. 3 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Oxfordshire. 2 records from Anymals+plants - Citizen Science Data. 141 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 76 records from Alterra (NL) - Entomofauna inventory in Amerongen forest. 19 records from Invertebrata Collection of Institute of Systematics and Evolution of Animals. 45 records from UAM Insect Observations (Arctos). 86 records from National Trust for Scotland - NTS Properties Species Records 1800-2013. 4580 records from Ground Beetle of Japan Specimen Database. 422 records from The Coleoptera collection (EC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 277 records from Countryside Council for Wales - Welsh Peatland Invertebrate Survey (WPIS). 92 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 13 records from Loopkevers Grensmaas - Ground beetles near the river Meuse in Flanders, Belgium. 3099 records from Carabidae of Poland. 2982 records from SGHN - Biota Galicia. 34 records from Bristol Regional Environmental Records Centre - BRERC October 2009. 37 records from Beetles (LSM). Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences